2020
DOI: 10.2337/db20-0062
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Absent Training-Induced Improvement in Insulin Action in Lean, Hyperandrogenic Women With Polycystic Ovary Syndrome

Abstract: Women with polycystic ovary syndrome (PCOS) have been shown to be less insulin sensitive compared with control (CON) women, independent of BMI. Training is associated with molecular adaptations in skeletal muscle, improving glucose uptake and metabolism in both healthy individuals and patients with type 2 diabetes. In the current study, lean hyperandrogenic women with PCOS (n 5 9) and healthy CON women (n 5 9) completed 14 weeks of controlled and supervised exercise training. In CON, the training intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 73 publications
0
32
0
Order By: Relevance
“…However, we report similar improvements in VO 2 peak in women with PCOS and Non-PCOS women after 16 weeks of HIT, which suggests that the six fewer HIT sessions performed by women with PCOS cannot fully explain the difference in training-induced improvements in fat oxidation rates. Absent training-induced improvements in women with PCOS have been reported previously; Hansen and colleagues observed improved insulin sensitivity measured by the gold-standard hyperinsulinaemic-euglycemic clamp in healthy women without PCOS, but not in women with PCOS after 14 weeks of exercise training (three weekly exercise sessions; two aerobic HIT sessions and one strength training session) (Hansen et al, 2020). Similarly, Hansen and colleagues reported improved incremental area under the oral glucose tolerance test curve for plasma glucose and insulin after exercise training in healthy women, but not in women with PCOS.…”
Section: Discussionmentioning
confidence: 74%
“…However, we report similar improvements in VO 2 peak in women with PCOS and Non-PCOS women after 16 weeks of HIT, which suggests that the six fewer HIT sessions performed by women with PCOS cannot fully explain the difference in training-induced improvements in fat oxidation rates. Absent training-induced improvements in women with PCOS have been reported previously; Hansen and colleagues observed improved insulin sensitivity measured by the gold-standard hyperinsulinaemic-euglycemic clamp in healthy women without PCOS, but not in women with PCOS after 14 weeks of exercise training (three weekly exercise sessions; two aerobic HIT sessions and one strength training session) (Hansen et al, 2020). Similarly, Hansen and colleagues reported improved incremental area under the oral glucose tolerance test curve for plasma glucose and insulin after exercise training in healthy women, but not in women with PCOS.…”
Section: Discussionmentioning
confidence: 74%
“…HIIT is a time-efficient training approach to stimulate biogenesis and increase skeletal muscle insulin sensitivity due to improvement of the mitochondrial function of the muscle; that is, the activation of the mitochondria receptors allows more energy to be produced and improves the maximum level of activity, increasing the skeletal oxidation capacity. In addition, antioxidant adaptations are superior in HIIT programs compared to continuous exercise of moderate intensity [31]. In part, these findings could justify a superior effect of HIIT in reducing the HOMA-IR parameter in relation to moderate-intensity exercise considering that oxidative stress seems to play an important role in the pathogenesis of insulin resistance [32,33].…”
Section: Plos Onementioning
confidence: 99%
“…A training modality that has had limited research in PCOS is resistance training. To date, only two studies employed resistance training alone in women with PCOS ( Almenning et al 2015 , Miranda-Furtado et al 2016 ), while other studies included a combined protocol of both aerobic and resistance training ( Bruner et al 2006 , Thomson et al 2008 , Hansen et al 2020 ). None of the studies with resistance training alone investigated mitochondrial characteristics, and only Almenning and colleagues assessed IR showing improvements in HOMA-IR in women with PCOS after the intervention.…”
Section: Effect Of Exercise On Mitochondrial Characteristics In Pcosmentioning
confidence: 99%
“…None of the studies with resistance training alone investigated mitochondrial characteristics, and only Almenning and colleagues assessed IR showing improvements in HOMA-IR in women with PCOS after the intervention. Of the three combined training interventions studies including both HIIT and resistance training, two did not measure IR but reported significant decreases in fasting insulin levels in women with PCOS ( Bruner et al 2006 , Thomson et al 2008 ), while Hansen et al showed improved insulin sensitivity (euglycaemic–hyperinsulinaemic clamp) in healthy women without PCOS, but not in lean women with PCOS ( Hansen et al 2020 ). In this study, the only mitochondrial characteristic measured in skeletal muscle was CS activity, which was increased by 65% in both women with and without PCOS after the 14-week intervention with no significant differences between groups ( Hansen et al 2020 ).…”
Section: Effect Of Exercise On Mitochondrial Characteristics In Pcosmentioning
confidence: 99%
See 1 more Smart Citation